Producing the Subject of Deportation. Filtration Processes during the Russia-Ukraine War - Getmanova, Daria; Matviyenko, Svitlana (Sociologica (Bologna), 2022)
The essay theorizes the "filtration process" executed by the Russian forces on the temporarily occupied Ukrainian territories that Ukrainian citizens undergo prior to their forceful deportation to the territory of the Russian Federation. The essay broadens the timeframe of "filtration" from interrogation to various logistical steps, including the digital and biometric data collection in so-called "camps," for instrumentalization and reification of deported civilians as data subjects.